Antithrombotic treatment in patients with stroke and supracardiac atherosclerosis. (4th August 2020) - Sagris, Dimitrios; Georgiopoulos, Georgios; Leventis, Ioannis; Pateras, Konstantinos; Pearce, Lesly A.; Korompoki, Eleni; Makaritsis, Konstantinos; Vemmos, Konstantinos; Milionis, Haralampos; Ntaios, George
Abstract : Objective: To compare the efficacy and safety of oral anticoagulants vs antiplatelets in patients with stroke and atherosclerotic plaques in the aortic arch or cervical or intracranial arteries, collectively described as supracardiac atherosclerosis. Methods: We searched PubMed and Scopus until August 28, 2019, for randomized trials comparing oral anticoagulants vs antiplatelets in patients with stroke and supracardiac atherosclerosis using the terms "anticoagulant or anticoagulation" and "antiplatelet or aspirin" and "randomized controlled trial or RCT" and "stroke or cerebral ischemia" and "aortic or carotid or vertebrobasilar or intracranial or atherosclerosis or stenosis or arterial." Four outcomes were assessed: recurrent ischemic stroke, major ischemic event or death, major bleeding, and intracranial bleeding. Treatment effects (relative risk [RR] and 95% confidence interval [CI]) were estimated by meta-analysis using random-effects models. Results: Among 1, 117 articles identified in the literature search, results from 10 randomized controlled trials involving 6, 068 patients with stroke/TIA with supracardiac atherosclerosis were included in the meta-analysis. Recurrent ischemic stroke rates were 2.94 per 100 patient-years in the anticoagulant-assigned patients vs 3.30 per 100 patient-years in the antiplatelet-assigned patients (RR, 0.91; 95% CI, 0.70–1.18 for the SJ estimator, I 2 = 26%). Major ischemic event or death rates were 4.39 per 100 patient-years in anticoagulant-assigned patients vs 4.32 in antiplatelet-assigned patients (RR, 1.03; 95% CI, 0.79–1.35; I 2 = 54.5%). Major bleeding rates were 2.88 per 100 patient-years in anticoagulant-assigned patients vs 0.82 in antiplatelet-assigned patients (RR, 3.21; 95% CI, 1.96–5.24; I 2 = 46%). Conclusion: This systematic review and meta-analysis showed that anticoagulant-assigned patients with stroke and supracardiac atherosclerosis were not at different risk of ischemic stroke recurrence and increased risk of major bleeding compared to antiplatelet-assigned patients.